2022
DOI: 10.1038/s41598-022-23138-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to monitor COVID-19 fatality rate in real-time, a key metric to guide public health policy

Abstract: An accurate estimator of the real-time fatality rate is warranted to monitor the progress of ongoing epidemics, hence facilitating the policy-making process. However, most of the existing estimators fail to capture the time-varying nature of the fatality rate and are often biased in practice. A simple real-time fatality rate estimator with adjustment for reporting delays is proposed in this paper using the fused lasso technique. This approach is easy to use and can be broadly applied to public health practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A real-time fatality rate estimator taking into account reporting delay in death has been recently proposed by Qu et al [ 6 ], where minimal epidemiological data, namely the observed time series of c t and d t , and the distribution F , are required as inputs. We will briefly mention the existing estimator to facilitate the discussion of its standardized version.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A real-time fatality rate estimator taking into account reporting delay in death has been recently proposed by Qu et al [ 6 ], where minimal epidemiological data, namely the observed time series of c t and d t , and the distribution F , are required as inputs. We will briefly mention the existing estimator to facilitate the discussion of its standardized version.…”
Section: Methodsmentioning
confidence: 99%
“…By setting p * = p 1 = ⋯ = p τ in ( 1 ), the above framework is reduced to that of the time-delay adjusted case fatality rate estimator studied in Nishiura et al [ 18 ], denoted as p * in this article. Given the strong serial correlation in the time series of p t and the fact that typically only the trend of the time series is of interest, Qu et al [ 6 ] proposed to apply the fused lasso technique [ 19 , 20 ] to obtain a smoothed estimator of p , namely the real-time delay-adjusted case fatality rate, henceforth rtaCFR t for t = 1, …, τ . Let d = ( d 1 , …, d τ ) T and be a ( τ − 1) × τ penalty matrix.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementing AI techniques like machine learning and deep learning can be crucial for rapid diagnosis and screening ( 29 ). This AI techniques may be beneficial for contact tracking and continuous monitoring of COVID-19 affected individuals ( 30 34 ). However, most advanced technology-enabled surveillance systems have been developed and deployed in high-income countries, leaving Bangladesh behind.…”
Section: Introductionmentioning
confidence: 99%